Signs of Media Logic: Half a Century of Political Communication in the Netherlands - Brants, Kees; van Praag, Philip (Javnost-The Public, 2006)
On the basis of three elections, covering a period of fifty years, the authors aim at testing the increasingly popular hypothesis that political communication is driven by media logic and by political and media system characteristics. In short: sooner or later, the modes and styles of American media will appear in Europe too. The complex and volatile relationship between media and politics in the Netherlands in the last half-century does show some, although not uni-linear signs of media logic. The strength of a public service tradition and a political culture of nonadversariality, however, seem to have stopped the developments short of a political communication style which is characterised by performance driven campaigning, horse race and poll driven reporting, orientation on the public as consumers, journalistic dominance, agenda setting and cynicism.